“Success was Actually Having Learned:” University Student Perceptions of Ungrading - Hasinoff, Amy A.; Bolyard, Wendy; DeBay, Dennis; Dunlap, Joanna C.; Mosier, Annika C.; Pugliano, Elizabeth (Teaching and Learning Inquiry, 2024)
A large body of evidence shows that many ungrading practices are as good or better than conventional approaches at supporting learning outcomes. Much of the research on student perceptions of ungrading, however, is based on individual case studies which, although informative, are often anecdotal, not systematically implemented, and tend to emphasize the instructor’s perspectives. Building on this literature, we offer a systematic study that asks: how do students perceive pedagogical practices designed by instructors to support an ungrading strategy? To answer this question, we conducted a survey of students across a range of disciplines and a variety of ungrading approaches to assess how they perceive their learning experiences in these courses as compared to others. Findings indicate that students generally perceive that ungrading practices improve their relationship with their instructor; enhance their engagement, agency, enjoyment, and interest; foster their intrinsic motivation and focus on learning; and facilitate their creativity. While many students reported reduced stress, others reported that the unfamiliarity and uncertainty of ungrading increased their stress. Gaining a better understanding of how students react to these pedagogical techniques can help instructors improve their practices. Read the corresponding ISSOTL blog post here.